Examining The Impact Of Accesibility Perceptionions On Prestige Motivation Among Visitors To Bromo Tengger Semeru National Park - Amanda Manda; Fitri Rahmafitri; Wanjat Kastolani (Politeknik Pariwisata Makassar, 2024)
This study aims to examine the influence of perceptions of accessibility to tourism on the prestige motivation of visitors to Bromo Tengger Semeru National Park, categorizing accessibility into physical and non-physical. This research employs a quantitative approach, utilizing multiple regression statistical analysis to explore the relationship between independent and dependent variables. 200 samples were obtained through a questionnaire distributed to Bromo Tengger Semeru National Park visitors who had visited at least once. The collected data were subsequently analyzed using multiple linear regression testing. The findings of this study reveal that: 1) perceptions of both physical and non-physical accessibility simultaneously influence the prestige motivation of visitors to Bromo Tengger Semeru National Park; 2) perceptions of physical accessibility, when analyzed separately, do not have an impact on prestige motivation, while perceptions of non-physical accessibility do have a significant effect; 3) the combined influence of perceptions of physical and non-physical accessibility on prestige motivation is relatively low, accounting for only 15.7%, while the remaining 84.3% is influenced by other variables not addressed in this study. This research recommends that future studies expand on the concepts of physical and non-physical accessibility by incorporating additional indicators based on other tourism theories.